The relationship between transformational leadership and organizational health in Golestan province of Iran - Khademfar, Mohammad; Idris, Khairuddin (2011)
This paper is carried out to determine the relationship between transformational leadership style and organizational health. The study attempted to determine if there is a difference in the teacher’s perception of the principal’s leadership style and school’s health. The population in this study consists of teachers in secondary schools in Golestan province of Iran. The researcher selected the cases by sample random sampling method. The result of reliability in pilot of study revealed that both instruments are reliable to administer the instrument, because the value of Cronbach’s Alpha for independent and dependent variable were high (.922, .915). In order to analyzing data the researcher has used descriptive statistics and a Correlation Pearson for related samples. The descriptive statistics provide a mean, range and standard deviation based on the results from both survey instruments.